The influence of menstrual cycle phase and urinary incontinence on potential ACL injury risk factors with a focus on hip strength and postural control in elite female team sport athletes: a pilot study - Kirschbaum, E. M.; Windisch, R.; Heyde, K.; Hunger, R.; Legerlotz, K. (Sports, 2026)
To improve understanding of anterior cruciate ligament (ACL) injuries, this study investigated the effect of menstrual cycle (MC) phase on ACL injury risk factors in elite female team sport athletes with and without urinary incontinence (UI). Additionally, associations between endogenous sex hormones, MC-related symptoms, and these risk factors were investigated. Ten elite female athletes (24.2 ± 3.6 years, BMI 23.2 ± 1.3 kg/m2, 10.9 ± 1.8 training hours/week) completed three testing sessions across three MC phases, determined using the three-step method. Assessments included static and dynamic postural control and hip strength. Mixed-model ANOVA and canonical correlation analyses evaluated the effects of MC phase, UI, hormones, and performance. A significant interaction between MC phase and UI was observed for single-leg sway area with eyes closed (p = 0.036), and UI was associated with a higher hip adduction:abduction ratio (p = 0.037). No further significant interaction between UI and MC phase was observed. Moreover, hormones explained 16.5% of the variance in risk factors, while subjective symptoms explained 24.5%. Lower progesterone was associated with higher symptoms, lower estradiol and progesterone with reduced strength and poorer postural control, and higher testosterone with greater strength. Although limited by its pilot design, menstrual symptoms, more than MC phases, may influence performance and injury risk, supporting the potential value of systematic symptoms monitoring.